16주간 복합운동프로그램 적용이 고령 남성 노인의 신체구성, 심혈관기능 및 최대근력에 미치는 효과 - 배지철; 김만겸; 김성철; 김홍 (Exercise science (Seoul, Korea), 2010)
본 연구의 목적은 16주간의 복합운동프로그램 적용이 고령 남성 노인에게 신체구성, 심혈관기능 및 최대근력에 어떠한 영향을 미치는지 규명하고, 고령 노인들에게 안전하고 효과적인 복합운동프로그램을 제시하는 데 있다. 본 연구의 대상자는 서울소재 S실버타운에 거주하면서 운동 참여를 제한하는 의학적 문제점이 없는 72세 이상의 고령 남성 노인 50명 중 복합운동프로그램에 95%이상 참여한 19명을 최종 선정하였다. 운동프로그램은 준비운동 10분, 본운동 40∼50분, 정리운동 10분, 일일 60∼70분, 주당 3회, 그리고 16주간 실시하는 복합운동으로 구성되었으며, 복합운동프로그램 참여 전ㆍ후에 모든 피험자들의 신체구성, 심혈관기능, 그리고 부위별 최대근력을 측정하였다. 연구결과, 16주간 복합운동프로그램 적용은 고령 남성 노인의 신체구성에 아무런 영향을 미치지 못했다. 또한 심혈관기능에 있어서도 통계적으로 유의한 변화는 없었다. 반면 16주간 복합운동프로그램 적용은 레그프레스를 제외한 모든 측정부위에서 최대근력을 통계적으로 유의하게 증가시켰다(p<.05). 이러한 연구결과는 적절한 운동은 고령 노인의 근력증가에 효과적이며, 제시된 16주간 복합운동프로그램은 고령 노인의 근력증가에 효과적인 운동프로그램이라고 할 수 있다. The purpose of this study is to investigate the effect of 16-week combined exercise on body composition, cardiovascular function, and maximal muscle strengthand to suggest safe and effective combined exercise program for old-old elderly male. Ninteen elderly male living in S silvertown regularly in Seoul (age 78.57±3.38 years) were finally selected as a subjects for this study because they have no medical problem for exercise and were involved over 95% in the combined exercise. The combined exercise program consits of 10 min warm-up, 40-50 min main exercise, and 10 min cool-down so subjectes exercised for 60-70 min a day, 3 times a week throughout 16 weeks. Data on body composition, cardiovascular function, and maximal muscle strength were measured by using bioelectrical impedance analysis, treadmill and other instrument, and various weight machines in each from all subjects before the start day of exercise and after the end day of exercise. The present results showed that 16-week combined exercise statistically have no positive effects on body composition and cardiovascular function in old-old elderly male. However, there were significant increases of maximal muscle strength in all measured part of the body except leg press and back extesion by 16-week combined exercise in old-old elderly male (p<.05). Therefore, this study suggested that combined exercise has an positive effect on increasing and maintaining muscle strength and the present 16-week combined exercise program is safe and effective for old-old elderly male. KCI Citation Count: 23